O Programa Nacional de Imunizações e os entraves à sua autossuficiência - Fernandes, Ramon de Lima (2022)
The present study sought to analyze how much the National Immunization Program (PNI) has advanced, over time, towards the desired self-sufficiency in immunobiologicals and what are the real obstacles to this self-sufficiency. For this, a bibliographic research of the entire history of the PNI was carried out, seeking to highlight the events that contributed to important changes in its direction, and current data on the acquisition of vaccines for use in humans by the PNI, including from imports, as well as data on technology transfers and vaccine patent filings in Brazil, which helped to understand the current functioning of the vaccine market in the country and how it affects the self-sufficiency of the PNI. Evidence indicates that, despite the worrying concentration of domestic vaccine production in few public laboratories, which can cause supply crises in exceptional periods, such as the recent coronavirus crisis (Covid-19), the greatest obstacle to PNI self-sufficiency it is technological dependence, since the expansion of the vaccine portfolio of public laboratories depends on technology transfers from foreign laboratories.